2016
DOI: 10.17722/jorm.v5i3.126
|View full text |Cite
|
Sign up to set email alerts
|

Is Customer Retention Beneficial for Customers: A Conceptual Background

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Thus, purchase punishment might be an issue that needs to be investigated intensively. For example, [10], [15] and [16] identified how punishments can be used to choose mobile phone service providers and even as a critical tool to block customers from switching to other providers. Another example that provided by [53] who identified how punishments can be used to make families adapt healthy food purchase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, purchase punishment might be an issue that needs to be investigated intensively. For example, [10], [15] and [16] identified how punishments can be used to choose mobile phone service providers and even as a critical tool to block customers from switching to other providers. Another example that provided by [53] who identified how punishments can be used to make families adapt healthy food purchase.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the main mobile phone contract dimensions is essential, due to the fact that the majority of previous studies have been done to investigate just one or few of the mobile contract elements as the following: contract price [11], text messaging [12], mobile phone brand [8], switching costs [13], customer satisfaction [14], customer retention determinants [6] [7] [15] [16], mobile application quality [17], ethical practices effect on maintaining relationship with customers [18], promotion mix effects on choosing a mobile phone supplier [19]. However, this study is targeting the main mobile phone contract elements that mobile phone suppliers can offer to customers.…”
Section: Introductionmentioning
confidence: 99%
“…As brand name and equity are often essential considerations these days, it would be good to explore parental choice for toy products with regard to a set of issues such as brand name, brand choice, parents' experience, marketing ethics, perceived usefulness and perceived enjoyment Alshurideh, 2016c). This study provides important findings for marketers and practitioners to develop new marketing strategies for selling toy products to consumers and for repeat buying (Alshurideh, 2009;Alshurideh, 2014b;Alshurideh, 2016aAlshurideh, , 2016b by the diversification of the selling of objects especially that relate to different consequences obtained.…”
Section: Conclusion Remarksmentioning
confidence: 99%
“…Hu et al (2009) indicated to deliver high quality services and created superior customer value, which can result in achieving high satisfaction, thus affecting the firm's corporate image and leading to consumer retention. In the mobile phone market, CR becomes an essential phenomenon since this sector has witnessed substantial growth, change, and competition (Alshurideh, 2016). Galetto (2015) indicated that the goals of 'customer retention' programs are to help companies secure as many customers as possible, often through loyalty and brand loyalty initiatives.…”
Section: Journal Of Management Researchmentioning
confidence: 99%
“…Galetto (2015) indicated that the goals of 'customer retention' programs are to help companies secure as many customers as possible, often through loyalty and brand loyalty initiatives. Alshurideh (2016Alshurideh ( , 2017 studied customer-retention behavior in the contractual and non-contractual mobile purchasing settings is essential, especially when the goal is to establish long-term customer relationships. How to prevent existing high ARPU subscribers from switching to competitors in the mobile industry is a very important issue.…”
Section: Journal Of Management Researchmentioning
confidence: 99%